Implementasi Model Project Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis dan Kreativitas pada Siswa Kelas IV MIN 2 Kota Surabaya - Mega Ilfi Nur Faidah; Munawir Munawir; Nasrul Fuad Erfansyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
In today's digital era, education is required to prepare students with critical and creative thinking skills as a provision to face real challenges. However, learning practices at MIN 2 Surabaya City are still dominant using a conventional teacher-centered approach, so student participation and creativity are low. This study aims to explore the effectiveness of the project based learning (PJBL) model in improving the critical thinking skills and creativity of grade IV students. The research method used was qualitative descriptive through observation and in-depth interviews with homeroom teachers and four students of grade IV A. The results of the study showed that PJBL was able to train students' critical thinking skills through problem-solving activities and stimulate creativity through real projects such as making dioramas and pop-up books. Despite the constraints of limited time and teacher experience, project-based learning (PJBL) has been proven to encourage more innovative, contextual, and relevant learning to the demands of the 21st century. This study confirms that PJBL deserves to be implemented more widely at the basic education level.